Exploring the Relationship between Diet and TV, Computer and Video Game Use in a Group of Canadian Children - Tomlin, Dona; McKay, Heather A.; Forster, Martina; Rhodes, Ryan E.; Rose, Hannah; Higgins, Joan Wharf; Naylor, Patti-Jean (International Journal of Child Health and Nutrition, 2014)
Increased screen-time has been linked to unhealthy dietary practices but most studies have looked primarily at television viewing or an amalgam. Therefore the purpose of this study was to investigate the relationship between specific screen-time (TV, computer, video game) and a selection of healthy dietary intake measures (calories, carbohydrate, fat, sugar, fruit, vegetables, fibre and sugar-sweetened beverages (SSB)) in a group of Canadian children. We used single day sedentary and dietary recalls to assess sedentary behaviour and diet in 1423 children (9.90 (0.58) y; 737 girls, 686 boys) from the Action Schools! BC Dissemination study. Correlations and multiple regression analyses were used to explore sedentary behaviour-diet relationships. TV and video game use were correlated with higher calories, fat, sugar and SSB consumption (r = 0.07 to 0.09; p <.01) and lower fibre intake (r = -0.05 to -0.06; p <.05). TV use was also correlated with lower fruit and vegetable intake. Regression analyses showed that when controlling for other variables, only TV and video game use predicted sugar and SSB consumption (β =.06 to.08; p <.05). Computer use was correlated with calories but did not significantly predict any of the measures of dietary intake. Although screen time was significantly associated with less healthy eating profiles, it did not account for much variance in dietary behaviour of these children.